2020
DOI: 10.1002/mar.21408
|View full text |Cite
|
Sign up to set email alerts
|

Feeling red lucky? The interplay between color and luck in gambling settings

Abstract: This paper investigates the effect of the color red on gambling behavior, as influenced by feeling lucky and cultural background. Four experiments examine how risk-taking choices and gambling behaviors are affected. Study 1A and 1B establish the red risk-aversion effect in gambling decision making and responses to a gambling app advert. Studies 2 and 3 test the moderating effect of feeling lucky and cultural background, respectively. The authors provide empirical evidence to the effect of red color on risk ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…In doing so, we recommend marketers employ language empowering consumers and underscoring their ability to help via their actions. Second, based on our findings related to risk aversion, noting the risk of non‐complaint behaviors is also of importance or designing ads in a manner to evoke risk aversion (e.g., using the color red; Pontes & Williams, 2021). Finally, policymakers may elect to employ advertising that highlights the guilt a consumer may feel if they fail to comply with COVID guidance.…”
Section: Discussionmentioning
confidence: 99%
“…In doing so, we recommend marketers employ language empowering consumers and underscoring their ability to help via their actions. Second, based on our findings related to risk aversion, noting the risk of non‐complaint behaviors is also of importance or designing ads in a manner to evoke risk aversion (e.g., using the color red; Pontes & Williams, 2021). Finally, policymakers may elect to employ advertising that highlights the guilt a consumer may feel if they fail to comply with COVID guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we identify two practical moderators based on metacognition theory and provide empirical evidence of their effectiveness in mitigating negative effects.Third, our research provides insights into the role of luck in consumer behavior. Previous research mainly focuses on how luckrelated concepts influence customers' feelings of uncertain outcomes(Jiang et al, 2009;Pontes & Williams, 2021). Recently,Hock et al (2020) demonstrated that lucky promotional game results induce positive customer affective attitude toward the marketer.…”
mentioning
confidence: 99%